Untangling the Meaning of Photos in Corporate Social Responsibility Reporting - Nabila Permatasari; Ani Wilujeng Suryani (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study aims to identify and analyze the meaning of photos in sustainability reports. Visual content analysis was used to determine the motives for using 1823 photos contained in 19 sustainability reports and 24 annual reports of mining companies. Mining companies are vulnerable to conflict because of the environmental pollution they cause; consequently, their legitimacy is threatened. The findings show that 32.58% of the total photos are community-related. Most photos depict the company's relationship with surrounding community groups. In addition, the company's CSR reports include several photos related to the environment, such as unpolluted nature. This is done in an effort to increase the company's legitimacy. Regarding employment practices and decent work, more photos of men than women are displayed, indicating that the mining industry is male-dominated. These findings provide a framework for informing and persuading stakeholders to appreciate the information presented in photographs.